Clinical Manifestation of Patients With Atypical Hemolytic Uremic Syndrome With the C3 p.I1157T Variation in the Kinki Region of Japan. (November 2018) - Matsumoto, Takeshi; Toyoda, Hidemi; Amano, Keishirou; Hirayama, Masahiro; Ishikawa, Eiji; Fujimoto, Mika; Ito, Masaaki; Ohishi, Kohshi; Katayama, Naoyuki; Yoshida, Yoko; Matsumoto, Masanori; Kawamura, Naohisa; et al.
The gain-of-function variation p.I1157T in C3 was previously identified in 8 patients with atypical hemolytic uremic syndrome (aHUS) at Mie University Hospital. In the present study, we identified another 11 patients with aHUS with this variation, including 10 pediatric patients (onset age: 1-16 years). The variation seems to be geographically concentrated around Mie Prefecture in Japan. Fifteen of the 19 patients with aHUS experienced infection as probable triggering events. All 19 patients had renal dysfunction. Seven patients, including 2 from the previous study and 5 from the present study, were treated with eculizumab, with all showing a good response with hematological normalization. Among the 5 eculizumab-treated patients in the present study, 3 had an ambiguous diagnosis of aHUS due to low-grade hemolysis even with elevated levels of lactate dehydrogenase and bilirubin. In those cases, in-house targeted DNA sequencing identified the C3 p.I1157T variation carriers, which enabled the early initiation of treatment with eculizumab. The present study supports the early introduction of eculizumab in patients with aHUS, especially pediatric patients.